Variation at the insulin gene VNTR (variable number tandem repeat) polymorphism and early growth: studies in a large Finnish birth cohort. - Bennett, A; Sovio, U; Ruokonen, A; Martikainen, H; Pouta, A; Taponen, S; Hartikainen, A; King, V; Elliott, P; Järvelin, MR; McCarthy, M (2004)
Variation at the insulin gene (INS-)VNTR (variable number of tandem repeats) minisatellite polymorphism has been reported to be associated with both early growth and adult metabolic phenotypes. However, the samples studied have been small and the relationship between INS-VNTR variation and parameters of early growth inconsistent, with four previous studies producing conflicting results. We have studied the relationship between INS-VNTR class (measured by genotyping the nearby -23HphI variant with which it is in tight linkage disequilibrium) and early growth in 5,646 members of the Northern Finnish Birth Cohort of 1966. Comparing class III homozygotes with other genotypes using multivariate linear regression analysis, we found no significant associations with any early growth measure (birth weight, birth length, ponderal index, and head circumference at 1 year), even after stratifying subjects by growth trajectory during infancy and/or birth order. For example, among infants with limited postnatal growth realignment (n = 2,470), class III/III infants were no heavier at birth (difference [+/-SE] in the means [fully adjusted], 58 +/- 51 g; P = 0.26) than class I/- infants. No significant associations were detected following reanalysis with an additive model (for example, for birth weight, beta = 20 g [95% CI -3 to 44], P = 0.09). Studies of this large population-based cohort have failed to generate convincing evidence that INS-VNTR variation influences early growth.